PENERAPAN LATIHAN PUSH-UP TERHADAP KETERAMPILAN PUKULAN MELINGKAR OLAHRAGA PENCAK SILAT PADA PERGURUAN CEMPAKA PUTIH DI DESA KARYA MULIA - Wawan Syafutra; Hengky Remora; M. Eric Kantona; Risma Isnani (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine the circular punching skills of pencak silat sports at the white cempaka college in Karya Mulia village after applying push-up exercises regularly. The research method used in this study is quantitative with an experimental approach with the design of One Group Pretest-Posttest Design. The sampling technique uses the Probability Sampling technique. The data collection techniques used in this study were initial tests and final tests. Based on the results of the study, it can be concluded that after applying push-up training, there is an influence on the circular punching skills of pencak silat sports at the white cempaka college in Karya Mulia Village. Looking at the paired sample test results, it shows a significant value between the pretest and posttest values with significance values (2-tailed) p = 0.00 < 0.05 t values calculated (14,281) > t table (1.796). This result also shows Ha: accepted and Ho: rejected